Probing the primordial helium abundance and the effective number of neutrino species with CMB - Perimeter Institute (Perimeter Institute, 2008)
We point out that light scalar fields with symmetries generically generate non-Gaussianity in the density fluctuations. Our observation makes the presence of the non-Gaussianity ubiquitous. When the inflationary scale and the properties of the scalar fields satisfy a certain relation, the non-Gaussianity becomes large enough to be observed by the ongoing and planned observations. We name such a particle responsible for a large non-Gaussianity as an \'ungaussiton\', and give explicit examples to realize the ungaussiton mechanism. We also derive a consistency relation between the bispectrum and the trispectrum, tau_NL = 10^3 f_NL^(4/3), which, if confirmed, will strongly support this mechanism.
Keywords: Quantum Fields and Strings; Particle Physics; Cosmology